الجريدة الرسمية العدد 47 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 3393 لسنة 2024 -- قرار رقم 3394 لسنة 2024 -- قرار رقم 3395 لسنة 2024 -- قرار رقم 3396 لسنة 2024 -- قرار رقم 3397 لسنة 2024 -- قرار رقم 3398 لسنة 2024 -- قرار رقم 3399 لسنة 2024 -- قرار رقم 3400 لسنة 2024 -- قرار رقم 3687 لسنة 2024 -- قرار رقم 3688 لسنة 2024 --